2022
DOI: 10.3390/nano12050779
|View full text |Cite
|
Sign up to set email alerts
|

Composition-Dependent Cytotoxic and Antibacterial Activity of Biopolymer-Capped Ag/Au Bimetallic Nanoparticles against Melanoma and Multidrug-Resistant Pathogens

Abstract: Nanostructured silver (Ag) and gold (Au) are widely known to be potent biocidal and cytotoxic agents as well as biocompatible nanomaterials. It has been recently reported that combining both metals in a specific chemical composition causes a significant enhancement in their antibacterial activity against antibiotic-resistant bacterial strains, as well as in their anticancer effects, while preserving cytocompatibility properties. In this work, Ag/Au bimetallic nanoparticles over a complete atomic chemical compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“… Lomelí-Marroquín et al (2019) reported that bimetallic Ag–Au NPs showed anticancer activity against human melanoma cells. Similarly, Nieto-Argüello et al (2022) confirmed that the use of bimetallic Ag–Au nanoparticles exhibits an anticancer impact on melanoma cells. This effect may be related to excessive ROS generated within the surrounding medium.…”
Section: Resultsmentioning
confidence: 59%
“… Lomelí-Marroquín et al (2019) reported that bimetallic Ag–Au NPs showed anticancer activity against human melanoma cells. Similarly, Nieto-Argüello et al (2022) confirmed that the use of bimetallic Ag–Au nanoparticles exhibits an anticancer impact on melanoma cells. This effect may be related to excessive ROS generated within the surrounding medium.…”
Section: Resultsmentioning
confidence: 59%
“…Previous studies reported that bimetallic nanoparticles have promising cytotoxic activities against cancerous cell lines. 80–85 Moreover, both cancerous MCF-7 and Caco 2 cell lines were used to evaluate bimetallic Ag–ZnO NPs, where bimetallic Ag–ZnO had promising anticancer activity, and IC 50 were 104.9 and 52.4 μg ml −1 , respectively. 81…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that bimetallic nanoparticles have promising cytotoxic activities against cancerous cell lines. [80][81][82][83][84][85] Moreover, both cancerous MCF-7 and Caco 2 cell lines were used to evaluate bimetallic Ag-ZnO NPs, where bimetallic Ag-ZnO had promising anticancer activity, and IC 50 were 104.9 and 52.4 mg ml −1 , respectively. 81 Additionally, bimetallic ZnO-Ag NPs were fabricated using laser ablation and results conrmed that bimetallic ZnO-Ag NPs have anticancer activity against the malignant cell lines HCT 116 and HeLa.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Research has employed biopolymer starch as a reducing and capping agent for the environmentally friendly, repeatable, and simple synthesis of Ag/Au bimetallic nanoparticles. These nanoparticles demonstrated excellent antimicrobial performance against multidrug-resistant Escherichia coli and methicillin-resistant Staphylococcus aureus, promoting wound healing and reducing scar formation [142]. Furthermore, Imran et al utilized zinc oxide (ZnO) coverage on biogenic gold nanoparticles obtained from Hibiscus plant extracts to synthesize Au@ZnO core-shell nanocomposites [140].…”
Section: Mnhh Based On Multiple Metal Materialsmentioning
confidence: 99%